Overexpression, purification and crystallization of the two C-terminal domains of the bifunctional cellulase ctCel9D-Cel44A from Clostridium thermocellum - Najmudin, Shabir (2005)
Clostridium thermocellum produces a highly organized multi-enzyme complex of cellulases and hemicellulases for the hydrolysis of plant cell-wall polysaccharides, which is termed the cellulosome. The bifunctional multi-modular cellulase ctCel9D-Cel44A is one of the largest components of the C. thermocellum cellulosome. The enzyme contains two internal catalytic domains belonging to glycoside hydrolase families 9 and 44. The C-terminus of this cellulase, comprising a polycystic kidney-disease module (PKD) and a carbohydrate-binding module (CBM44), has been crystallized. The crystals belong to the tetragonal space group P43232, containing a single molecule in the asymmetric unit. Native and seleno-l-methionine-derivative crystals diffracted to 2.1 and 2.8 Å, respectively.